2019
DOI: 10.1515/zpch-2019-1449
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemistry of Ferrites: Theoretical Predictions vs. Experimental Results

Abstract: This paper gives an overview about recent theoretical and experimental work on electronic and optical properties of spinel ferrites MFe2O4. These compounds have come into focus of research due to their possible application as photocatalyst material for photoelectrochemical water splitting. The theoretical background of state-of-the-art quantum-chemical approaches applied for predicting electronic and optical band gaps, absolute band positions, optical absorption spectra, dielectric functions and Raman spectra,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 161 publications
4
21
0
Order By: Relevance
“…3 B), the E g band (189 cm −1 ) is due to the asymmetric and symmetric bending of O with respect to Fe, the F 2g (1) band (107 cm −1 ) is due to the translational movement of the whole tetrahedron (FeO 4 ), and the A 1g band (630 cm −1 ) is due to the symmetric stretching of oxygen atoms along Fe–O (or Mn–O) tetrahedral bonds 14 . The bands confirm the inverse spinel structure of the MnFe 2 O 4 43 . The Raman spectrum of the MnFe 2 O 4 /MoS 2 nanocomposite coated on a nickel foam shows the peaks due to MnFe 2 O 4 and also the F 2g (2) band, which is due to the asymmetric stretching of Fe/Mn–O bonds, as well as the E 2 g band of few-layer MoS 2 nanosheets, confirming the presence of both MnFe 2 O 4 and MoS 2 in the nanocomposite.…”
Section: Resultssupporting
confidence: 63%
“…3 B), the E g band (189 cm −1 ) is due to the asymmetric and symmetric bending of O with respect to Fe, the F 2g (1) band (107 cm −1 ) is due to the translational movement of the whole tetrahedron (FeO 4 ), and the A 1g band (630 cm −1 ) is due to the symmetric stretching of oxygen atoms along Fe–O (or Mn–O) tetrahedral bonds 14 . The bands confirm the inverse spinel structure of the MnFe 2 O 4 43 . The Raman spectrum of the MnFe 2 O 4 /MoS 2 nanocomposite coated on a nickel foam shows the peaks due to MnFe 2 O 4 and also the F 2g (2) band, which is due to the asymmetric stretching of Fe/Mn–O bonds, as well as the E 2 g band of few-layer MoS 2 nanosheets, confirming the presence of both MnFe 2 O 4 and MoS 2 in the nanocomposite.…”
Section: Resultssupporting
confidence: 63%
“…Ulpe and co-workers investigated in depth the electronic structure of several spinel materials, confirming that the band gap description is challenging for DFT calculations. 52 Herein, the calculated values at PBE0 allowed us to relate the increased band gap value to the variation in the Ni amount, which is in agreement with previous experimental data. 54,55 Another important aspect to consider about the electronic structure of CNF nanoparticles is the atomic state localization along the valence/conduction bands.…”
Section: Magnetic and Electronic Structure Analysissupporting
confidence: 89%
“…The calculated values showed excellent agreement with previous theoretical and experimental data. 25,51,52 In particular, it was observed that the calculated dielectric constant was reduced as the Ni amount was increased. However, all values were calculated in the range of 7.1-7.9, indicating that all models exhibit good electrical properties for energy-harvesting applications.…”
Section: Dielectric Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…In the Raman spectrum of MnFe2O4 nanoparticles, the Eg band (189 cm -1 ) is due to the asymmetric and symmetric bending of O with respect to Fe, the F2g(1) band (107 cm -1 ) is due to the translational movement of the whole tetrahedron (FeO4), and the A1g band (630cm -1 ) is due to the symmetric stretching of oxygen atoms along Fe-O (or Mn-O) tetrahedral bonds13 . The bands confirm the inverse spinel structure of the MnFe2O434 . The Raman spectrum of the MnFe2O4/MoS2 nanocomposite shows the peaks due to MnFe2O4 and also the F2g(2) band that is due to the asymmetric stretching of Fe/Mn-O bonds as well as the E2g band of few-layer MoS2 nanosheets, confirming the presence of both MnFe2O4 and MoS2 in the nanocomposite.…”
supporting
confidence: 62%